A Conceptual Analysis of Food Parenting Practices in the Light of Self-Determination Theory: Relatedness-Enhancing, Competence-Enhancing and Autonomy-Enhancing Food Parenting Practices - Di Pasquale, Roberta; Rivolta, Andrea (Frontiers in Psychology, 2018)
The relationships between parenting behaviors and child obesity or obesogenic eating behaviors (i.e. overeating unhealthy food) have been studied through the use of different parenting constructs; in particular, specific food parenting practices have been extensively investigated, but there is currently a need for a more comprehensive and integrative theoretical framework to guide future investigations. The present article argues for the use of Self-determination theory as a valuable framework to conceptually organize food parenting practices relevant to children’s obesogenic eating behaviors. The three parenting dimensions of positive parental involvement, autonomy support and provision of structure - highlighted by Self-determination theory as closely linked to the process of internalization of healthy behaviors and values by the child - will be adopted as a framework to categorize food parenting practices into three types of practices: relatedness-enhancing, competence-enhancing and autonomy-enhancing.